Dari Teks ke Wacana: Interpretasi Kontekstual Al-Qur’an dalam Hermeneutika Nasr Hamid Abu Zayd: From Text to Discourse: A Contextual Interpretation of the Qur’an in Nasr Hamid Abu Zayd’s Hermeneutics - Shofiatul Jannah; Hairus Saleh; Umi Kulsum; Tarmidzi (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2026)
This study examines the dialectical relationship between text and reality in the hermeneutics of Nasr Hamid Abu Zayd, particularly his understanding of the Qur’an as both a linguistic phenomenon and a cultural product. Abu Zayd argues that the Qur’an did not emerge in a historical vacuum, but was revealed within specific socio-historical, linguistic, and cultural contexts. From this perspective, he critiques rigid and ahistorical interpretations that separate the Qur’an from the realities of human life. This study employs a library research approach combined with thematic and hermeneutical analysis to explore the transformation of the Qur’an from a static text (mushaf) into a living discourse that continuously interacts with changing historical and social realities. The novelty of this study lies in its analysis of Abu Zayd’s hermeneutics not merely as a method of interpretation, but as an epistemological transformation that shifts the Qur’an from a fixed text toward a dialogical and contextual discourse. In addition, this study shows that Abu Zayd’s ideas generated intellectual debates concerning religious authority, interpretation, and the relationship between revelation and contemporary human experience. Ultimately, this study argues that Abu Zayd’s hermeneutics represents a critique of interpretive traditions that freeze the meaning of the Qur’an within rigid textual authority.